RESPON KECEPATAN TIMBILNYA ESTRUS DAN LAMA ESTRUS PADA BERBAGAI PARITAS SAPI PERANAKAN ONGOLE (PO) SETELAH DUA KALI PENYUNTIKAN PROSTAGLANDIN F2α (PGF2α) - Irmaylin SM; Madi Hartono; Purnama Edy Santosa (JURNAL ILMIAH PETERNAKAN TERPADU, 2014)
The research aimed to: (1) determine the response of estrous onset of Ongole Offspring at thevarious parities after the injection of prostaglandin F2α (PGF2α) twice; (2) determine the responseof estrous duration of Ongole Offspring at the various parities after the injection of prostaglandinF2α (PGF2α) twice. The research was held in November until December 2012, located in PunggurDistrict, Central Lampung Regency, Lampung Province. This research used CompletelyRandomized Design (CRD) with three treatments and four replications. The treatments wereOngole Offspring heifers (P0); Ongole Offspring which have calved once (P1); and OngoleOffspring which have calved twice (P2). The variables observed was performed statistically byanalysis of variance on level of 5% or 1%. The result of the research showed that parity was notsignificantly different (P>0,05) on the estrous onset and the estrous duration of Ongole Offspringat the various parities after prostaglandin F2α (PGF2α) injection twice. The estrous onset ofOngole Offspring at the various parities after the injection of prostaglandin F2α (PGF2α) twice P0,P1, P2 in a row were 45,57; 43,26; 52,53 hours, whereas the estrous duration of Ongole OffspringPO P0, P1, P2 in a row were 13,58; 18,65; 15,72 hours.